Preschool spontaneous focusing on numerosity predicts rational number conceptual knowledge 6 years later - Jake McMullen; Minna M. Hannula-Sormunen; Erno Lehtinen (Springer, 2022)
Recent evidence suggests that early natural number knowledge is a predictor of later rational number conceptual knowledge, even though students’ difficulties with rational numbers have also been explained by the overuse of natural number concepts—often referred to as the natural number bias. Hannula and Lehtinen (Learn Instr 15:237–256, 2005) have shown that children’s tendency to spontaneously focus on numerosity (SFON) predicts the development of natural number and arithmetic skills. The present study follows 36 children from the age of 6 years to the age of 12 years in order to determine how preschool SFON tendency and number  sequence skills are related to rational number conceptual knowledge at the age of 12 years.  The results show that children’s SFON tendency before school age is a strong predictor of later
rational numbers conceptual knowledge, even after controlling for preschool number sequence skills. This finding has implications for the understanding of how the transition from reasoning about natural number concepts to reasoning about rational numbers may be influenced by children’s self-initiated practice with numbers in everyday situations.